Penyusunan Standard Operating Procedure untuk Software Management dan Software Development pada Perusahaan XYZ berdasarkan Pedoman Information Technology Infrastructure Library - Dwi Cindy Herta Turnip; Admaja Dwi Herlambang; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Perusahaan XYZ is part of the Badan Usaha Milik Negara (BUMN). Perusahaan XYZ in managing its Information Tecnology is obliged to follow BUMN Ministerial Regulation number PER-03/MBU/02/2018. In response to these BUMN regulations, Perusahaan XYZ formed the 2018-2022 RITI. The plan explains that Perusahaan XYZ will prepare IT Governance Guidelines which contain SOP (Standard Operating Procedure) and also Directors' Regulations in 2018/2019. The establishment of the IT SOP is based on the Software Development and Management domain on ITIL (Information Tecnology Infrastructure Library) framework. In compiling the SOP, the first will be an interview with the Departemen Pengembangan dan Pemeliharaan Sistem (PPS) as the role responsible for the Software Development and Software Management process. Then a GAP analysis will be conducted to see the gap between current conditions and ideal conditions in the company. From the results of the gap a suggestion will emerge to equalize it. This proposal will later be included in the activities compiled with the flowchart format in the SOP Draft produced later. The end result is an SOP design for the Software Development process which produces 6 activities and 16 sub-activities. It also produced an SOP for the Software Management process which resulted in 5 activities and 12 sub-activities.